(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article deals with the role of the Ukrainian theater of coryphaei’s in establishing the Ukrainian national identity on the basis of work of D. Antonovych, M. Voronyi, Y. Mamontov, memoirs of L. Staritska-Chernyahivska. The article focuses on the means of influence of Ukrainian theater spectators in the end of XIX – beginning of the XX century.